Income poverty and well-being among vulnerable households: a study in Malaysia - Ahmad, Nor Fairani; Mansor, Mariani; Paim, Laily (Canadian Center of Science and Education, 2016)
The paper aims to examine the income poverty status and compare it with the well-being level between different groups among vulnerable households. Vulnerable households for this study were households that consists at least one of the following criteria: income poor, elderly person, single mothers and/or disabled person. Data was taken from the Official Poverty Line Survey conducted in four Malaysian cities representing each region in Peninsular Malaysia. A total of 286 households were conveniently selected. Descriptive statistics such as mean, standard deviation, ANOVA, correlation tests were applied in data analysis. Findings indicated significant differences in household percapita income (HHPCI) among income poverty status groups and significant differences in well-being among different status of income poverty, whereby the non-poor had the highest mean in both (HHPCI & well-being). Also the mean well-being for poor and potential poor groups were much lower than the hardcore poor group. Further results revealed a positive but small relationship between household percapita income and well-being among vulnerable households. Finally, the findings indicated significant differences between income poor status groups and different level in well-being poor groups. It was possible for people to get out of income poverty while remaining in well-being deprivation (ill-being). Findings from this study provide evidences and enhance understanding in income poverty, well-being and correlates of both especially among vulnerable households.